OP83 Contribution of Behavioural Risk Factors and Socio-Economic Position to Mortality in British South Asian and European Adults: 17 year follow-up of the Newcastle Heart Project Cohort. (10th September 2013) - Tran, A; Hayes, L; McNally, R; Unwin, N; Bhopal, R; White, M
Abstract : Background: British South Asians experience excess cardiovascular disease (CVD) morbidity and mortality. Evidence for this is often based on studies using place of birth as a proxy for ethnicity. We examined the contribution of CVD risk factors and socio-economic position (SEP) to mortality in Europeans and South Asians, who provided confirmation of their ethnicity. Methods: South Asian and European origin individuals, aged 25–74 years, were recruited (April 1993 to March 1997). Ethnicity was determined by self-identified ancestry; at least 3 grandparents born in India, Pakistan or Bangladesh indicated South Asian ethnicity. Lifestyle, SEP, biochemical and anthropometric data were collected. Participants were mortality flagged with the NHS Medical Research Information Service. A lifestyle risk score, including BMI and self-reported physical activity, diet, smoking and alcohol consumption (range 0–5) was dichotomised to categorise a 'healthy' (score 0–2) or 'unhealthy' lifestyle (score 3–5). SEP was determined by the occupation of the head of the household. Age-adjusted hazard ratios (HR) for death were derived from Cox regression analyses. Results: 817 Europeans and 684 South Asians were followed up for 12-17 years. Mean follow-up was 14.9 and 13.9 years for Europeans and South Asians respectively. 5 Europeans and 34 South Asians were lost to follow-up, most commonly because individuals were no longer NHS registered (2 Europeans, 27 South Asians). Mortality ratios, standardised to a Newcastle-upon-Tyne European population, for Europeans and South Asians were 76.5 and 60.3 respectively (z-test of significance for difference between ethnic groups, p = 0.168). 28% and 49% of European men and women respectively (chi-square for difference, p < 0.001), and 23% and 26% (South Asian men and women, NS) were classified as having a healthy lifestyle. Having an unhealthy lifestyle was significantly associated with mortality in European women only (HR 1.8; 95% CI 1.03, 3.25). SEP was associated with mortality in European women and South Asian men (HR for manual vs non-manual occupation 3.1 [1.3, 7.5] and 3.7 [1.4, 9.9] respectively). SEP attenuated the effects of lifestyle on mortality in further models. Conclusion: No significant difference in SMR between Europeans and South Asians found at 12–17 years of follow-up, although in contrast to previous studies we report a higher SMR in Europeans than in South Asians. There was a trend towards higher mortality in those with a less healthy lifestyle, but this was statistically significant only in European women. Adjusting for SEP attenuated the relationship between lifestyle and mortality suggesting that both SEP and lifestyle influence mortality.